Development and rasch validation of the student mental health scale among Indonesian university students - Yusuf, Syamsu; Budiman, Nandang; Saripah, Ipah; Afendy, Popy Mayasari; Gofur, Ridwan; Hamidah, Nur'aini Hasna (ProGCouns: Journal of Professionals in Guidance and Counseling, 2025)
Mental health among university students is a critical issue that affects academic performance, quality of life, and overall well-being. This study aims to develop and validate the Student Mental Health Scale (SMHS), a culturally contextualized instrument designed to assess mental health status among Indonesian university students. Utilizing a quantitative, cross-sectional design, data were collected from students across nine faculties at Universitas Pendidikan Indonesia. The Rasch Model was employed for data analysis, providing precise and objective insights into mental health distribution. Results indicated that 19.8% of students demonstrated healthy mental status, 59.5% experienced moderate mental health concerns, and 20.6% exhibited poor mental health. These findings suggest that approximately 80% of university students require mental health support, highlighting the urgent need for comprehensive campus-based interventions. Key stressors include academic pressures, social dynamics, and financial burdens, with female students showing greater vulnerability. Effective interventions, such as peer support programs and resilience training, are therefore essential. This study underscores the importance of distinguishing between universal mental health instruments and culturally adapted tools, with the SMHS filling a critical gap by providing contextually appropriate assessments that international scales cannot adequately capture in Indonesian university settings. The findings hold significant implications for mental health interventions and institutional strategies in higher education.